SARS-CoV-2 RNA in plasma is associated with ICU admission and mortality in patients hospitalized with COVID-19 - Prebensen, Christian (Clin Infect Dis, 2020)
The clinical significance of SARS-CoV-2 RNA in the circulation is unknown. In this prospective cohort study, we detected viral RNA in the plasma of 58/123 (47%) patients hospitalized with COVID-19. RNA was detected more frequently, and levels were higher, in patients who were admitted to the ICU and/or died.